Assessment of potential thrombogenicity in an animal model of a triple viral inactivated Factor IX Concentrate Manufactured in Argentina - Martinez, M. C. (2021)
The risk of thromboembolism with FIX replacement therapy remains a concern for hemophilic B patients. Previous studies from our laboratory demonstrated that the activated factor content of the FIX Plasma Derived (FIXpd) manufactured at UNC-Hemoderivados was negligible by in vitro assay. Despite this, we considered it important to conduct studies to assess the potential thrombogenic risk of our FIXpd concentrates using a modified stasis animal model. FIXpd were inject doses of 100 or 200 IU F IX kg-1 and some samples were supplemented with heparin (<0.5 of heparin/ IU FIX). Eight rats were tested at each dose level in the presence or absence of heparin, considering those samples with a thrombogenicity ≥2.0 as of potential thrombogenic risk. The mean scores ± SD 100 and 200 IU kg-1 in the presence or absence of heparin were 0.25±0.06 and 2.25±0.45 and 1.19±0.26 and 2.81±0.40, respectively. At both doses tested of FIXpd in the absence of heparin, there was no significant difference in mean scores (P<0.05). The encouraging data obtained from these animal experiments and results from in vitro tests, support the low thrombotic risk associated with the FIXpd concentrate manufactured in UNC Hemoderivados.